Effects of herbal marinades on the shelf-life of chilled chicken ‘Satay’ / Faridah Ahamad - Faridah, Ahamad (Faculty of applied Sciences, 2008)
Effects of herbal marinades in term of antioxidant and antimicrobial of three types of Malaysian herbs namely Curry leaf (Murraya koenigii), ‘Kesum’ leaf (Polygonum minus huds) and ‘Ulam Raja’ (Cosmos caudatus) were investigated against lipid oxidation and microbial growth in chicken ‘satay’ during storage at -4°C for 12 days. The antioxidative activities were compared to chicken ‘satay’ formulation without herbal mixtures (Control) and with synthetic antioxidant BHA/BHT. Formulations with herbal mixtures (F1) (0.31%), with twice the amount of herbal mixtures (F2) (0.61%) and with BHA/BHT showed significantly lower Thiobarbituric Acid Values (TBA) and Peroxides Values (PV) compared to the Control. Addition of either herbal mixtures (0.31% or 0.61%) or BHA/BHT (0.02%) significantly delayed lipid oxidation when compared to the Control. The antioxidant of the different samples added were in the descending order, F1>BHA/BHT>F2>Control. On the other hand, the initial Total Plate Count and Mould and Yeast Count in the samples ranged from 5.1 to 5.7 log10 CFU/ml and 3.7 to 4.5 log10 CFU/ml respectively. Addition of herbal mixtures and BHA/BHT slightly reduced microbial counts when compared to control at 0 day. All the samples were spoiled on day 3 onwards in both microbial tests except for BHA/BHT in mould and yeast count which started to spoil at day 6. Sensory analysis indicated that overall panelist’s acceptability toward the samples followed the order: Control>F1>F2. The results suggested that herbal mixtures of Curry leaf (Murraya koenigii), ‘Kesum’ leaf (Polygonum minus huds) and ‘Ulam Raja’ (Cosmos caudatus) could be another potential source of natural food ingredients to preserve meat products.